HOW TO MANAGE SUCCESSFULLY PROBLEMATIC EMPLOYEES AT WORKPLACE: USEFUL FEEDBACKS FOR MANAGERS. - S.X.Oʻrinboyeva (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract: Effective management of employees is one of the main management tasks of every leader. However, the question of how to successfully manage problematic employees remains a common problem among many leaders today. Bad behavior of one employee in the company, bad relationship with the manager or colleagues has a negative impact on the work of other members in the team. A decrease in work efficiency can seriously damage the company's operations in the future, as well as the company's profits. Managing problem employees is a difficult process for managers, but it is necessary to take immediate measures to minimize the damage to the company. This article discusses what the term "problem employee" means, the problematic situations they cause, their reasons, and effective ways to resolve them. Also, the manager's tasks in creating a positive and healthy environment in the company were highlighted.